EPID-22. RACIAL AND ETHNIC DIFFERENCES IN ADULT GLIOMA INCIDENCE AND SURVIVAL IN THE UNITED STATES. (5th November 2018) - Ostrom, Quinn; Cote, David; Ascha, Mustafa; Kruchko, Carol; Barnholtz-Sloan, Jill
Abstract: BACKGROUND: Glioma is the most commonly occurring malignant brain tumor in the United States (US), and incidence and survival varies by age, sex, and race/ethnicity. The goal of this analysis was to estimate the racial and ethnic differences in glioma incidence and survival by histologic subtype. METHODS: Data were obtained from the Central Brain Tumor Registry of the US (incidence data from ~99.9% of the US), and the Surveillance, Epidemiology and End Results program (survival data for ~28% of the US). Histology-specific age-adjusted incidence rates were generated by race, Hispanic ethnicity, sex, and age groups. Histology-specific relative survival rates were generated by race, Hispanic ethnicity, treatment type, insurance status, and age. RESULTS: Overall incidence of glioblastoma, non-glioblastoma astrocytoma, and oligodendroglial tumors were higher among White non-Hispanic (WNH) individuals than among any other group. Most tumors were more common in males than in females across all race/ethnic groups. The majority of tumors occurred in those aged 40+ years, with differences in incidence by race/ethnicity appearing in all three age groups. Survival after diagnosis was similar among non-WNH individuals, but was lower among WNH individuals for glioblastoma, irrespective of treatment. Survival after diagnosis with glioblastoma among those that receive chemo-radiation remains higher in non-WNH groups after adjustment for age and extent of resection. CONCLUSION: US. Incidence and survival patterns of most glioma histologies varied significantly by race/ethnicity, with WNHs having higher incidence and lower survival compared to individuals of other racial and ethnic groups. Further examination is necessary in order to determine the factors contributing to these differences.